NLRC5/MHC class I transactivator is a target for immune evasion in cancer - Yoshihama, Sayuri (Proc Natl Acad Sci U S A, 2016)
Cancer cells develop under immune surveillance, thus necessitating immune escape for successful growth. Loss of MHC class I expression provides a key immune evasion strategy in many cancers, although the molecular mechanisms remain elusive. MHC class I transactivator (CITA), known as “NLRC5” [NOD-like receptor (NLR) family, caspase recruitment (CARD) domain containing 5], has recently been identified as a critical transcriptional coactivator of MHC class I gene expression. Here we show that the MHC class I transactivation pathway mediated by CITA/NLRC5 constitutes a target for cancer immune evasion. In all the 21 tumor types we examined, NLRC5 expression was highly correlated with the expression of MHC class I, with cytotoxic T-cell markers, and with genes in the MHC class I antigen-presentation pathway, including LMP2/LMP7, TAP1, and β2-microglobulin. Epigenetic and genetic alterations in cancers, including promoter methylation, copy number loss, and somatic mutations, were most prevalent in NLRC5 among all MHC class I-related genes and were associated with the impaired expression of components of the MHC class I pathway. Strikingly, NLRC5 expression was significantly associated with the activation of CD8(+) cytotoxic T cells and patient survival in multiple cancer types. Thus, NLRC5 constitutes a novel prognostic biomarker and potential therapeutic target of cancers.